Co-bedding of multiples in the neonatal unit: Assessing nurses and midwives attitude and level of understanding - Adams, C.; Gill, Fenella (Elsevier Ltd, 2014)
Abstract Aim: The purpose of this project was to explore the existing attitudes andlevel of understanding of nurses and midwives towards co-bedding multiples (twinsand higher order multiples) in a large Australian, tertiary level, Neonatal Unit.Method: A purposefully designed anonymous survey was first piloted and thendistributed to nurses and midwives working in the neonatal unit. Respondents wererequired to answer eight multiple choice questions to assess their level of understandingof co-bedding and rate eight statements, using a 5-point Likert scale, to assesstheir attitude towards the practice.Findings: A total of 201 surveys were distributed and 148 surveys were returned, resultingin a response rate of 74%. A mean of 85% of respondents answered the multiplechoice questions correctly. Seventy four percent of the respondents agreed with theeight statements that described potential benefits of co-bedding (47% agreed and 27%strongly agreed), 16% were undecided and 10% disagreed.Conclusion: This project has demonstrated that the nurses and midwives understoodand held positive attitudes towards the practice of co-bedding of multiples. It appearsthat there is sufficient support to move forward to implement this aspect of familycentred care best practice for neonates who are medically stable.